THE ANALYSIS OF CONSOLIDATION PROCESS OF CLAY SOILS FROM CAUSED BY THE DUTY PROCESS IN ERECTIONS THE ROAD BED OF HIGHWAYS - Timofeeva, L. M. (Science and Transport Progress, 2010)
The analysis of consolidation process of condensed water-saturated clay soils of the floodable bridge-approach fill to the bridge across Kama River, erected by method called «Intensive technology», is presented. The method consists in the arrangement of drainage longitudinal and cross-section cuts for acceleration of consolidation of soils of the road bad and the base composed from the weak, strongly compressible water-saturated clay soils of different consistency.